Covert observation in practice: lessons from the evaluation of the prohibition of smoking in public places in Scotland - Ritchie Deborah; Eadie Douglas; Creely Kaen S; Hilton Shona; Semple Sean; Petticrew Mark; Ferrell Catherine; Christopher Yvette; Hurley Fintan (BMC, 2007)
Abstract Background A ban on smoking in wholly or substantially enclosed public places has been in place in Scotland since 26th March 2006. The impact of this legislation is currently being evaluated in seven studies, three of which involve direct observation of smoking in bars and other enclosed public places. While the ethical issues around covert observation have been widely discussed there is little practical guidance on the conduct of such research. A workshop was therefore convened to identify practical lessons learned so far from the Scottish evaluation. Methods We convened a workshop involving researchers from the three studies which used direct observation. In addition, one of the fieldwork managers collected written feedback on the fieldwork, identifying problems that arose in the field and some solutions. Results There were four main themes identified: (i) the difficulty of achieving and maintaining concealment; (ii) the experience of being an observer; (iii) the risk of bias in the observations and (iv) issues around training and recruitment. These are discussed. Conclusion Collecting covert observational data poses unique practical challenges, in particular in relation to the health and safety of the researcher. The findings and solutions presented in this paper will be of value to researchers designing similar studies.